2011
DOI: 10.1089/neu.2010.1738
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Restores sAPPα Levels and Reduces the Late Histopathological Consequences of Traumatic Brain Injury in Mice

Abstract: Traumatic brain injury (TBI) induces both focal and diffuse lesions that are concurrently responsible for the ensuing morbidity and mortality and for which no established treatment is available. It has been recently reported that an endogenous neuroprotector, the soluble form α of the amyloid precursor protein (sAPPα), exerts neuroprotective effects following TBI. However, the emergent post-traumatic neuroinflammatory environment compromises sAPPα production and may promote neuronal degeneration and consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 59 publications
(77 reference statements)
2
43
0
Order By: Relevance
“…Short-term administration of minocycline (similar to the paradigm used in study 1) has been found effective in decreasing microglial activation following neonatal hypoxic ischemia (Cai et al, 2006; Cikla et al, 2016; Fan et al, 2006; Lechpammer et al, 2008), pediatric cardiac arrest (Tang et al, 2010), neonatal repetitive TBI (Hanlon et al, 2016), and adult TBI (Bye et al, 2007; Homsi et al, 2010; Siopi et al, 2011). The reduction in activated microglia was accompanied by an attenuation of neuronal damage (Cikla et al, 2016), a decrease in asphyxia-induced neurodegeneration (Tang et al, 2010), and a reduction of lesion volume following TBI (Homsi et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Short-term administration of minocycline (similar to the paradigm used in study 1) has been found effective in decreasing microglial activation following neonatal hypoxic ischemia (Cai et al, 2006; Cikla et al, 2016; Fan et al, 2006; Lechpammer et al, 2008), pediatric cardiac arrest (Tang et al, 2010), neonatal repetitive TBI (Hanlon et al, 2016), and adult TBI (Bye et al, 2007; Homsi et al, 2010; Siopi et al, 2011). The reduction in activated microglia was accompanied by an attenuation of neuronal damage (Cikla et al, 2016), a decrease in asphyxia-induced neurodegeneration (Tang et al, 2010), and a reduction of lesion volume following TBI (Homsi et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In the neonate, HI-induced microglial activation and the concomitant oligodendrocyte cell death, myelin loss and decrease in white matter volume were attenuated by minocycline (Cai et al, 2006; Fan et al, 2006; Lechpammer et al, 2008). In the adult mouse, TBI-induced loss of corpus callosum volume was attenuated by minocycline treatment (Siopi et al, 2011). In contrast, short-term administration of minocycline in the present study did not affect axonal injury or degeneration, an observation that was similar to those in a model of repetitive brain trauma in the neonate rat (Hanlon et al, 2016) and closed head injury in the adult mouse (Homsi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59,60 Moreover, in several TBI models, minocycline, which has antiinflammatory properties, has been shown to reduce histopathological consequences after mTBI in mice. 61,62 Of particular interest is a recent study by Siopi and collaborators that demonstrated that reducing neuroinflammation post-injury attenuated memory impairment in a mouse model of CHI; 63,64 however, more work is required to address the impact of microglial activation on cognitive function after TBI.…”
Section: Discussionmentioning
confidence: 99%